(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
High-intensity interval training (HIIT), also known high-intensity intermittent exercise (HIIE) or sprint interval training (SIT), is a form of interval training, a cardiovascular exercise strategy alternating short periods of intense anaerobic exercise with less intense recovery periods. There is no universal HIIT session duration, these intense workouts typically last under 30 minutes, with times vary on a participant’s current fitness level. The intensity of HIIT depends on the duration of the session. HIIT workouts provide improved athletic capacity and condition as well as improved glucose metabolism.